Analisis Kelayakan Penerapan Produksi Bersih pada Industri Amplang (Studi Kasus UMKM Risma Amplang Desa Takisung) - Muhammad Indra Darmawan; Almira Ulimaz; Nuraini Dwi Cahyani (Agriculture Faculty, 2025)
Amplang processing produces waste in the form of solid and liquid waste that can cause environmental pollution, including the UMKM Risma Amplang owned by Mrs. Faridatul Aina in Desa Takisung. This study aims to analyze the potential and alternative proposed implementation of cleaner production in UMKM Risma Amplang and determine alternative priorities for implementing cleaner production based on technical aspects and economic potential. The method used in this study is to use material balance and quick scanning to identify the process flow of amplang processing and alternative applications of cleaner production. Furthermore, the alternative clean production is carried out by technical analysis using a pairwise comparison questionnaire and Expert Choice. The technically selected alternative will be analyzed for its economic potential. Based on several eligibility criteria, an alternative to the proposed implementation of cleaner production that can be done at UMKM Risma Amplang is to make crackers from the skin and bones of mackerel fish, buy ingredients (sugar, salt, flavoring, baking soda) with a larger size, replacing the use of packaged tapioca flour brands with sacks of tapioca flour brands, making bath soap using used cooking oil, replacing the use of cloves of garlic with garlic powder. The priority of alternative clean production in terms of technical and economic aspects is the manufacture of crackers with a profit of Rp.452,000 in 1 month.